2021
DOI: 10.1021/acs.jproteome.1c00220
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Age, Sex, and Diet on the Human Fecal Metabolome Investigated by 1H NMR Spectroscopy

Abstract: The human fecal metabolome is increasingly studied to explore the impact of diet and lifestyle on health and the gut microbiome. However, systematic differences and confounding factors related to age, sex, and diet remain largely unknown. In this study, absolute concentrations of fecal metabolites from 205 healthy Danes (105 males and 100 females, 49 ± 31 years old) were quantified using 1 H NMR spectroscopy and the newly developed SigMa software. The largest systemic variation was found to be highly related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 65 publications
2
13
1
Order By: Relevance
“…This discrepancy may be because the study by Barton et al was performed as a long-term fitness intervention, while the present study only included baseline fitness levels of free-living community-dwelling older adults who have not (yet) been under specific physical training. Moreover, the older subjects in this study showed significantly lower concentrations of SCFAs than younger, 18-years-old, subjects did, as previously reported [26]. However, the increased concentrations of SCFAs in LF subjects may also be explained by the altered regulation of glucose transport, fatty acid oxidation, and steroid biosynthesis in LF subjects compared to HF subjects [36,37], and this increase has also been related to different rates of glucose homeostasis and lipid metabolism between HF and LF subjects [38].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This discrepancy may be because the study by Barton et al was performed as a long-term fitness intervention, while the present study only included baseline fitness levels of free-living community-dwelling older adults who have not (yet) been under specific physical training. Moreover, the older subjects in this study showed significantly lower concentrations of SCFAs than younger, 18-years-old, subjects did, as previously reported [26]. However, the increased concentrations of SCFAs in LF subjects may also be explained by the altered regulation of glucose transport, fatty acid oxidation, and steroid biosynthesis in LF subjects compared to HF subjects [36,37], and this increase has also been related to different rates of glucose homeostasis and lipid metabolism between HF and LF subjects [38].…”
Section: Discussionsupporting
confidence: 90%
“…It has been shown that LF subjects were eating more protein than the HF subjects [14]. Although this difference in protein consumption does not influence the fecal AA levels, it weakly affects the isovaleric acid and propionic acid levels [26]. In feces, AAs derive from the endogenous metabolism of the gut microbiome [39], and the effect of fitness on changing fecal AA levels is elusive [40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, the gut microbiome also plays a pivotal role in shaping systemic immune responses and is known to influence the efficacy of immune checkpoint inhibitors [35,36]. Despite the knowledge of the influence of sex, age and diet on the gut microbiome, little is known to what extent these parameters can affect the response to immunotherapy [37,38].…”
Section: Discussionmentioning
confidence: 99%